1994
DOI: 10.1002/j.2161-1874.1994.tb00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Leader in Therapy Groups Conducted With Illicit Drug Abusers: How Directive Does the Leader Have to Be?

Abstract: A 17‐hour marathon group was conducted in a residential treatment center established for inmates in a correctional setting in the southeastern United States. The Hill Interaction Matrix (HIM‐G; Hill, 1965) was used to measure the types of leader activity and the types of member activity during portions of each hour of the group activity. It was found that when the group was most therapeutic, there was a relationship between the therapists' actions and behaviors and the types of issues that were discussed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Subsequent process studies of unstructured marathon groups with male illicit drug users revealed the following: Group members ranked at the 99th percentile in time spent in the most therapeutic (confrontive) work style (Page & Bridges, 1983;Page, Davis, Berkow, & O'Leary, 1989), at the 80th percentile in time spent in the most therapeutic (relationship) content style (Page & Wills, 1983), and at the 90th percentile in the two of the four most therapeutic cells (personal-confrontive and relationship-confrontive; L. Campbell & Page, 1993). Page, Campbell, and Wilder (1994) showed that illicit drug abusers can interact in therapeutic ways without relying on group leaders to direct discussions. When considered together, the outcome and the process studies conducted by Page and his associates strongly suggest that unstructured-existential marathon groups can be used as an effective form of treatment for inmate and illicit drugusing populations.…”
Section: Research On Existential Group Psychotherapymentioning
confidence: 99%
“…Subsequent process studies of unstructured marathon groups with male illicit drug users revealed the following: Group members ranked at the 99th percentile in time spent in the most therapeutic (confrontive) work style (Page & Bridges, 1983;Page, Davis, Berkow, & O'Leary, 1989), at the 80th percentile in time spent in the most therapeutic (relationship) content style (Page & Wills, 1983), and at the 90th percentile in the two of the four most therapeutic cells (personal-confrontive and relationship-confrontive; L. Campbell & Page, 1993). Page, Campbell, and Wilder (1994) showed that illicit drug abusers can interact in therapeutic ways without relying on group leaders to direct discussions. When considered together, the outcome and the process studies conducted by Page and his associates strongly suggest that unstructured-existential marathon groups can be used as an effective form of treatment for inmate and illicit drugusing populations.…”
Section: Research On Existential Group Psychotherapymentioning
confidence: 99%
“…The dimension that captured the greatest empirical attention in the latest process studies was that of leader behavior. Researchers have examined what the leader says (Flowers & Booraem, 1990a, 1990bKapur, 1993;Kennard, Roberts, & Winter, 1990;Nehls, 1992;Page, Campbell, & Wilder, 1994;Stinchfield & Burlingame, 1991;Voigt & Weininger, 1992), thinks about (Hines, Stockton, & Morran, 1995;Kivlighan & Quigley, 1991), and values (Hamblin, Beutler, Scogin, & Corbishley, 1993). Although methodological sophistication varied widely across these studies, they all seem committed to identifying specific in-group leader behaviors, both overt and covert, that make a difference either in terms of patient responses that immediately follow the therapist intervention (known as small " 0 " ) or ultimate outcome (i.e., big "0').…”
Section: Process Analysis In Therapeutlc Groupsmentioning
confidence: 99%